Light / acid / solvent triple response type MOF (Metal Organic Framework) material as well as preparation method and application thereof
By designing a photo/acid/solvent triadic responsive MOF material and utilizing the three-dimensional network structure of tpt and tpdc-4F ligands, the independent response of the MOF material to light, acid and solvent stimulation was realized, which solved the problems of insufficient stability and sensitivity of existing MOF materials and enhanced the multifunctional integration capability.
Patent Information
- Application Number
- CN202511372589.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-24
- Publication Date
- 2026-01-27
AI Technical Summary
The stimulus-response performance of existing MOF materials mostly depends on a single mechanism, resulting in poor stability, irreversible response, or insufficient sensitivity. Furthermore, traditional ligand design ignores the synergistic effect of flexible frameworks and multiple sites, which limits the integration of multiple functions.
The design and synthesis selects electron-deficient tpt and H2tpdc-4F ligands to form a three-dimensional network structure through coordination of metal nodes with tpt and tpdc-4F ligands. Triple response is achieved by utilizing light, acidic environment and solvent molecule changes. Independent regulation is achieved through photoisomerization of tpt ligand, protonation of carboxylic acid group of tpdc-4F and reconstruction of hydrogen bond network, respectively.
Independent responses of MOF materials to light, acid, and solvent stimulation were achieved, improving the sensitivity and stability of the materials, avoiding response interference, and enhancing multifunctional integration capabilities.
Smart Images

Figure CN121405958A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal complex technology, specifically to a photo / acid / solvent triple-responsive MOF material, its preparation method, and its applications. Background Technology
[0002] Metal-organic frameworks (MOFs), as novel crystalline porous materials, possess advantages such as designable framework structures, high specific surface areas, regular pore structures, and ease of functionalization, and have shown potential applications in gas adsorption and separation, luminescence, heterogeneous catalysis, and sensing. Theoretically, the properties of MOFs can also be altered by adjusting the electronic states of the framework. Despite the challenges, achieving the control of the electronic states of MOF materials has high research value, especially in optics-related fields.
[0003] The optical properties of MOFs can be modulated through various means, including external stimuli (such as light, pressure, and temperature), host-guest interactions, metal ion exchange, or ligand conformational changes. For example: pressure-sensitive MOFs, such as PCN-128, achieve fluorescence color changes (470nm→537nm) through conformational twisting of tetraphenylethylene ligands, showing potential in pressure sensing. Multistimulus-responsive MOFs, such as Zr7 cluster-modified viologen-based MOFs, enhance response sensitivity by shortening the electron donor-acceptor distance, exhibiting rapid responses to X-rays, ultraviolet light, temperature, and organic ammonia vapor. Acid-responsive MOFs, such as Zr-O cluster-based MOFs, achieve significant conductivity changes through protonation of pyridine sites; however, high acid concentrations can lead to performance degradation due to anion interference.
[0004] Current MOF stimulus-response performance largely relies on a single mechanism, and some materials suffer from poor stability, irreversible response, or insufficient sensitivity. Furthermore, traditional MOF ligand design often neglects the synergistic effect of flexible frameworks and multiple sites, limiting their multifunctional integration. Summary of the Invention
[0005] To comprehensively address the above-mentioned problems, this invention aims to provide a photo / acid / solvent triple-responsive MOF material, its preparation method, and its application, thereby satisfying the sensitivity of MOFs to multiple synergistic responses in complex application scenarios.
[0006] Technical concept: The idea of this invention is to construct MOFs with potential stimulus-response behavior by designing and synthesizing selectively electron-deficient tpt and H2tpdc-4F.
[0007] The first aspect of this invention provides a photo / acid / solvent triple-responsive MOF material, with the chemical formula as follows:
[0008] [M(tpt)(tpdc-4F)(NOH)]n;
[0009] Wherein, M is any one of the group IIB elements Cd and Zn; tpt is 2,4,6-tris(4-pyridyl)-1,3,5-triazine; tpdc-4F is 3,3″,5,5″-tetrafluoro-[1,1′:4′,1″-triphenyl]-4,4″-dicarboxylic acid; NOH is a C1-C4 alcohol molecule.
[0010] Through the above technical solution, the coordination of metal nodes with TPT and TPDC-4F ligands forms a three-dimensional network structure. Under illumination, the triazine ring of the TPT ligand undergoes photoisomerization, altering the electronic transition path; in an acidic environment, the protonation degree of the carboxylic acid group of TPDC-4F changes, causing framework contraction; when the solvent molecule replaces NOH, the hydrogen bond network reconstruction leads to a shift in the fluorescence emission wavelength. These three response mechanisms do not interfere with each other under steric hindrance, allowing for independent regulation.
[0011] Preferably, M is Cd, a Group IIB element, then the chemical formula of the MOF material is [Cd(tpt)(tpdc-4F)(NOH)]. n .
[0012] Through the above technical solution, cadmium ions form coordination bonds with the pyridine group of the TPT ligand and the carboxylic acid group of TPDC-4F, constructing a three-dimensional framework structure. Simultaneously, NOH molecules fill the channels through dynamic hydrogen bonding. Under illumination, the triazine group of TPT undergoes electronic transitions with the fluorine substituent of TPDC-4F, leading to changes in fluorescence emission. In an acidic environment, protonation of the carboxylic acid group causes local deformation of the framework, releasing NOH molecules. Solvent polarity changes are responded to through rearrangement of the hydrogen bond network within the channels. Cadmium's coordination ability and ionic radius are conducive to forming a highly crystalline framework, avoiding irreversible responses caused by metal node instability.
[0013] Preferably, M is Zn, a group IIB element, then the chemical formula of the MOF material is [Zn(tpt)(tpdc-4F)(NOH)]. n .
[0014] Through the above technical solution, zinc ions form coordination bonds with the pyridine group of the TPT ligand and the carboxylic acid group of TPDC-4F to construct a three-dimensional porous framework. Fluorine-modified TPDC-4F protonates the material under acidic conditions through electronic effects, triggering changes in fluorescence signal. NOH alcohol molecules achieve solvent response through a dynamic adsorption-desorption process. The d10 electronic configuration of zinc ions enhances the fluorescence efficiency of the framework, while its coordination stability is superior to that of cadmium ions, allowing the material to maintain structural integrity during repeated stimulation cycles.
[0015] The second aspect of this invention provides a method for preparing a photo / acid / solvent triple-responsive MOF material, comprising the following steps: S1, reacting 18-crown-6, KOH, and 4-cyanopyridine in decahydronaphthalene by heating, followed by acid / base treatment to obtain tpt ligand; S2, condensing 1,4-dibromobenzene and 3,5-difluoro-4-methoxyformylphenylboronic acid pinacol ester under palladium catalyst, followed by hydrolysis to obtain H2tpdc-4F ligand; S3, heating tpt, H2tpdc-4F, and M(NO3)2·4H2O in a DMF / ethanol mixed solvent to obtain MOF crystals.
[0016] Through the above technical solutions, in the preparation of TPT ligands, the synergistic effect of 18-crown-6 and KOH can enhance the cyclization reaction rate of 4-cyanopyridine, and the triazine ring structure can be directionally assembled by controlling the heating temperature and time. The acid / base treatment step can remove unreacted cyanopyridine and byproducts, avoiding interference from impurities in subsequent MOF assembly. In the synthesis of H2tpdc-4F ligands, the palladium catalyst catalyzes the coupling reaction through oxidative addition and transmetalation mechanisms; the introduction of fluorine atoms can enhance the ligand electronic effect and improve the MOF's response sensitivity to acid stimulation. In the MOF crystal growth stage, the mixing ratio of DMF and ethanol can adjust the coordination rate between metal ions and ligands, and heating can promote Cd... 2+ Coordination crosslinking with TPT and TPDC-4F forms a rigid framework structure with photoresponsiveness.
[0017] Preferably, in S1, the mass ratio of 18-crown-6 to 4-cyanopyridine is 1:10.
[0018] Using the above technical solution, in a decahydronaphthalene solvent system, 18-crown-6 forms a complex with potassium hydroxide, transferring cyanopyridine from the organic phase to the reaction interface. When the mass ratio of crown ether to cyanopyridine is controlled at 1:10, a sufficient concentration of potassium ion-crown ether complex can be maintained to promote trimerization kinetics, while avoiding excess crown ether from hindering product crystallization. Heating at this ratio allows cyanopyridine to undergo directional condensation into a triazine ring in an alkaline environment. After acid treatment to remove unreacted monomers, high-purity TPT ligands are obtained.
[0019] Preferably, in S2, the molar ratio of 1,4-dibromobenzene and 3,5-difluoro-4-methoxybenzeneboronic acid pinacol ester is 1:3.
[0020] Using the above technical solution, in the presence of a palladium catalyst, the two bromine atoms of 1,4-dibromobenzene undergo two coupling reactions with three equivalents of borate ester to form a terphenyl framework structure. When the molar ratio is set to 1:3, it ensures that each bromine atom reacts with 1.5 equivalents of borate ester, thereby fully consuming the halogenated product during the condensation stage and reducing byproduct formation. This ratio design is based on a balance between the number of reaction sites and reagent activity; excess borate ester can drive the reaction forward without increasing costs due to excessive reagent waste. After the reaction is complete, the intermediate product is hydrolyzed to remove the methoxyformyl group, ultimately yielding the H2tpdc-4F ligand with specific fluorine substitution sites.
[0021] Preferably, in S3, the molar ratio of pt, H2tpdc-4F and M(NO3)2·4H2O is 1:1:(1.5-2.5).
[0022] Through the above technical solution, in the DMF / ethanol mixed solvent system, TPT and H2TPDC-4F provide rigid support and flexible connection functions in an equimolar ratio, while the metal salt ensures sufficient coordination at a molar ratio of 1.5-2.5. This ratio allows the metal center to preferentially coordinate with carboxylic acid groups to form secondary units, which are then linked through pyridine groups to form a three-dimensional framework. When the amount of metal salt is less than 1.5 times, incompletely coordinated carboxylic acid groups will cause disordered stacking; when it is more than 2.5 times, excess metal ions will occupy ligand sites, leading to structural collapse.
[0023] Preferably, in S3, M(NO3)2·4H2O is either Cd(NO3)2·4H2O or Zn(NO3)2·4H2O.
[0024] The third aspect of this invention provides an application of a photo / acid / solvent triple-responsive MOF material prepared as described above, for use in the preparation of optical products, such as fluorescent luminescent products.
[0025] The beneficial effects of this invention are:
[0026] (1) This material forms a three-dimensional network structure through coordination of metal nodes with TPT and TPDC-4F ligands. Under illumination, the triazine ring of the TPT ligand undergoes photoisomerization, altering the electronic transition path; in an acidic environment, the protonation degree of the carboxylic acid group of TPDC-4F changes, causing framework contraction; when the solvent molecule replaces NOH, the hydrogen bond network reconstruction leads to a shift in the fluorescence emission wavelength. The three response mechanisms do not interfere with each other under steric hindrance, achieving independent regulation.
[0027] (2) By synthesizing TPT and TPDC-4F ligands stepwise, the integrity of the ligand structure can be precisely controlled; optimizing the molar ratio of 1,4-dibromobenzene to fluorophenylboronic acid ester can reduce side reactions; and using a DMF / ethanol mixed solvent system can simultaneously increase Cd. 2+ The dispersion and ligand coordination activity of the MOF materials were improved, which solved the framework defect problem caused by impure ligand synthesis in existing MOF materials. High crystallinity MOF crystals were obtained through stepwise purification. Attached Figure Description
[0028] Figure 1 This is a flowchart of the preparation method of the present invention;
[0029] Figure 2 This is a schematic diagram of the synthesis of the tpt ligand of the present invention, and the tpt ligand in CDCl3. 1 H-NMR spectrum, schematic diagram of H2tpdc-4F ligand synthesis, and H2tpdc-4F ligand in DMSO 1 H-NMR spectrum;
[0030] Figure 3 This is a schematic diagram of the synthesis of MOF material and a CdS topology network diagram of Embodiment 1 of the present invention;
[0031] Figure 4 It is the triple interpenetrating framework of the MOF material in Embodiment 1 of the present invention;
[0032] Figure 5 This is a schematic diagram of the structure of the tpt ligand of the present invention, which is inserted into the metal-dicarboxylic acid rhombic framework through coordination of two pyridine N groups.
[0033] Figure 6 These are the thermal stability results of Embodiment 1, Embodiment 2, Comparative Example 1, and Comparative Example 4 of the present invention;
[0034] Figure 7 This is a schematic diagram of the MOF material of Embodiment 1 of the present invention after being exposed to HCl vapor and then fumigated with NH3 under sunlight and ultraviolet light, a solid UV-Vis spectrum of the MOF material after HCl fumigation, a fluorescence emission spectrum of the MOF material after HCl vapor fumigation, and a fluorescence emission spectrum of the MOF material after fumigation with different acid vapors.
[0035] Figure 8 This is a schematic diagram of the contour lines of the frontier molecular orbitals HOMO and LUMO before and after protonation of the MOF material in Embodiment 1 of the present invention.
[0036] Figure 9The images show the solid-state UV-Vis spectrum of the MOF material after being fumigated with HCl vapor for different times, the solid-state fluorescence spectrum of the MOF material after being fumigated with HCl vapor for different times, the fluorescence decay curves of the MOF material before and after being fumigated with HCl vapor, and the contour lines of the frontier molecular orbitals HOMO and LUMO of the MOF material before and after protonation.
[0037] Figure 10 This is a schematic diagram of the response of the MOF material in Embodiment 1 of the present invention under different wavelengths of light;
[0038] Figure 11 These are the solid-state UV-Vis spectra of the MOF material in Embodiment 1 of the present invention after being irradiated with a xenon lamp for different times, the fluorescence emission spectra of the MOF material after being fumigated with HCl vapor, the fluorescence emission spectra of the MOF material after five cycles of xenon lamp-induced color change, and the electron paramagnetic resonance spectra of the MOF material before and after xenon lamp irradiation.
[0039] Figure 12 These are the X-ray diffraction patterns and Fourier transform infrared spectra of the MOF material in Example 1 of this invention before and after xenon lamp irradiation.
[0040] Figure 13 These are the solid-state UV-Vis spectrum and fluorescence emission spectrum of the MOF material in Example 2 of this invention after being irradiated with a xenon lamp for different times;
[0041] Figure 14 This is the fluorescence emission spectrum of the MOF material of Example 2 of the present invention after 5 cycles of xenon lamp photochromism;
[0042] Figure 15 These are the X-ray diffraction patterns and electron paramagnetic resonance patterns of the MOF material in Example 2 of this invention before and after xenon lamp irradiation.
[0043] Figure 16 The images show the solid-state 3D fluorescence emission spectrum of the MOF material in Example 1 of this invention, the normalized fluorescence emission spectrum of the MOF material dispersed in different solvents (Ex = 365 nm), the normalized fluorescence emission spectrum of the MOF material dispersed in MeOH / DMF mixed solvents with different proportions, the emission spectrum of the MOF material, the PXRD spectrum of the MOF material after different treatments, and the fluorescence decay spectrum of the MOF material after different treatments.
[0044] Figure 17 The normalized emission spectra of the MOF material of Example 1 of the present invention dispersed in different ethanol / methanol mixed solvents, and the normalized emission spectra of the MOF material of Comparative Example 1 obtained by exchanging the directly synthesized MOF material with methanol.
[0045] Figure 18 The Hirshfeld surface plots of the dnorm, shape-index, and fingerprint mapping of the MOF materials of Embodiment 1 and Comparative Example 1 of this invention are shown.
[0046] Figure 19 The diagram shows the contour lines of the frontier molecular orbitals HOMO and LUMO of the MOF materials in Embodiment 1 and Comparative Example 1 of this invention, as well as the contour lines of the frontier molecular orbitals HOMO and LUMO of the MOF materials in Comparative Examples 1-3.
[0047] Figure 20 This is the solid-state 3D fluorescence spectrum of the MOF material in Example 2 of the present invention;
[0048] Figure 21 The normalized emission spectra of the MOF material of Example 2 of the present invention dispersed in different solvents (Ex = 365 nm) and the normalized emission spectra of the MOF material dispersed in mixed solvents of different proportions of ethanol / methanol are shown.
[0049] Figure 22 This is a schematic diagram of the orbital contour lines of the frontier molecular orbitals HOMO and LUMO of the MOF materials of Example 2 and Comparative Example 4 of the present invention.
[0050] Figure 23 The d of the MOF materials of Example 2 and Comparative Example 4 of this invention norm Hirshfeld surface plot with shape-index and fingerprint mapping;
[0051] Figure 24 This is a schematic diagram illustrating the application of the MOF material in fluorescent luminescent products according to Embodiment 1 of the present invention. Detailed Implementation
[0052] The following combination Figures 1-24 The preferred embodiments of the present invention are described herein. It should be understood that the preferred embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0053] The raw materials and reagents involved in this invention are as follows:
[0054] All solvents used in this invention are commercially available analytical grade reagents. N,N-dimethylformamide, N,N-diethylformamide, methanol, ethanol, acetonitrile, and dichloromethane were purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd., while 18-crown-6, 4-cyanopyridine, decahydronaphthalene, 1,4-dibromobenzene, 3,5-difluoro-4-methoxycarboxyphenylboronic acid pinacol ester, cesium carbonate, tetrakis(triphenylphosphine)palladium, Cd(OTF)3, and Zn(OTF)3 were purchased from Shanghai Bid Pharmaceutical Technology Co., Ltd.
[0055] A photo / acid / solvent triple-responsive MOF material has the chemical formula: [M(tpt)(tpdc-4F)(NOH)]n; where M is any one of Group IIB elements Cd or Zn; tpt is 2,4,6-tris(4-pyridyl)-1,3,5-triazine; tpdc-4F is 3,3″,5,5″-tetrafluoro-[1,1′:4′,1″-terphenyl]-4,4″-dicarboxylic acid; and NOH is a C1-C4 alcohol molecule. Specifically, if M is a Group IIB element Cd and N is an ethanol molecule, then the MOF material is [Cd(tpt)(tpdc-4F)(EtOH)]. n It belongs to the monoclinic crystal system, with space group C2 / c and cell parameters of . α=90°, β=93.438(7)°, γ=90°, If M is a group IIB element Zn and N is an ethanol molecule, then the MOF material is [Zn(tpt)(tpdc-4F)(EtOH)]n, belonging to the monoclinic crystal system, space group C2 / c, and cell parameters are... α=90°, β=91.581(2)°, γ=90°,
[0056] Figure 1 This is a flowchart of a method for preparing a photo / acid / solvent triple-responsive MOF material according to an embodiment of the present invention. The preparation method includes the following steps: S1, 18-crown-6, KOH, and 4-cyanopyridine are heated and reacted in decahydronaphthalene, followed by acid / base treatment to obtain tpt ligand; S2, 1,4-dibromobenzene and 3,5-difluoro-4-methoxyformylphenylboronic acid pinacol ester are condensed under the action of palladium catalyst, and then hydrolyzed to obtain H2tpdc-4F ligand; S3, tpt, H2tpdc-4F and M(NO3)2·4H2O are heated in a DMF / ethanol mixed solvent to obtain MOF crystals.
[0057] Example
[0058] Example 1
[0059] A method for preparing a photo / acid / solvent triple-responsive MOF material includes the following steps:
[0060] S1. Dissolve 3.0 g of 18-crown-6, 0.675 g of KOH, and 30.0 g of 4-cyanopyridine in 30 mL of decahydronaphthalene. Repeatedly vacuum the mixture under N2 atmosphere and heat to 200 °C for 4 h. The reaction system turns wine-red. After cooling to room temperature, add 50 mL of acetone and stir thoroughly. Filter to obtain a crystalline crude product. Wash the crude product repeatedly with acetone, dry it, dissolve it in 60 mL of concentrated hydrochloric acid, filter to remove insoluble impurities, and add excess ammonia to the filtrate to produce a white flocculent precipitate. Wash with water until neutral. After drying in air, 18 g of the target product is obtained, with a yield of approximately 61%. Figure 2 (a) in the diagram is a schematic diagram of the synthesis of ligand tpt;
[0061] S2. Add 1.18 g and 5 mmol of 1,4-dibromobenzene, 3.24 g and 15 mmol of pinacol 3,5-difluoro-4-methoxycarboxyphenylboronic acid, 6.5 g and 20 mmol of cesium carbonate, and 350 mg and 0.3 mmol of tetra(triphenylphosphine)palladium to a 500 mL Schlenk flask in sequence. Connect a condenser to the flask, then connect it to a vacuum line, evacuate the flask, and purge with nitrogen. Repeat this process three times. Then, place 250 mL of 1,4-dioxane in a 500 mL round-bottom flask, degas it three times using liquid nitrogen, and transfer the 1,4-dioxane to the Schlenk flask. Stir at 85°C for 3 days under a nitrogen atmosphere. After the reaction was complete, the solvent was evaporated to room temperature and the reaction product was washed with water and extracted with a large amount of CH2Cl2. The organic phase was separated and collected. The residual Pd powder in the organic phase was filtered off using a silica gel filter through a sintered glass funnel. The organic phase was dried with anhydrous Na2SO4, and the solvent was evaporated to obtain the crude product. The crude product was dissolved in EA and separated by column chromatography to obtain product E. Product E and 3M KOH solution were added to 200 mL of 1,4-dioxane, and the mixture was heated under reflux at 110 °C for 24 h. After the reaction was complete, the mixture was cooled to room temperature, the solvent was evaporated to dryness, water was added and stirred for 2 h, the pH was adjusted to 2 with HCl, and a precipitate was formed. The precipitate was filtered to obtain the white solid product H2tpdc-4F.
[0062] S3. Weigh 5.5 mg, 0.017 mmol of tpt, 7.0 mg, 0.017 mmol of H2tpdc-4F, and 11.0 mg, 0.035 mmol of Cd(NO3)2·4H2O into a 5 mL glass vial. Then add 1.5 mL of a mixed solution of N,N-dimethylformamide (DMF) and 1.5 mL of ethanol (EtOH). After sonication for 30 min, react at 85 °C for 72 h to obtain colorless blocky single crystals. Filter and collect the crystals, wash with hot DMF, and vacuum dry at 45 °C to obtain colorless blocky crystals [Cd(tpt)(tpdc-4F)(EtOH)]n.
[0063] Example 2
[0064] A method for preparing a photo / acid / solvent triple-responsive MOF material differs from Example 1 in step S3. In S3, tpt (5.5 mg, 0.017 mmol), H2tpdc-4F (7.0 mg, 0.017 mmol), Zn(NO3)2·6H2O (9.5 mg, 0.032 mmol), ethanol (EtOH, 1.5 mL), and N,N-dimethylformamide (DMF, 1.5 mL) are placed in a 5 mL glass vial and sonicated for 30 min. The mixture is heated in an oven at 85 °C for 24 h, and after cooling to room temperature, colorless bulk crystals [Zn(tpt)(tpdc-4F)(EtOH)]n are obtained, with a yield of 67%.
[0065] Comparative Example 1
[0066] A method for preparing a derivative of a photo / acid / solvent triple-responsive MOF material includes the following steps: 20 mg of the colorless bulk crystals obtained in Example 1 are weighed into a 20 mL glass vial and dispersed in 10 mL of MeOH. The solution is heated in an oven at 85 °C for 20 h, and then cooled to room temperature to obtain colorless bulk crystals [Cd(tpt)(tpdc-4F)2(MeOH)2]n.
[0067] Comparative Example 2
[0068] A method for preparing a derivative of a photo / acid / solvent triple-responsive MOF material includes the following steps: 20 mg of colorless bulk crystals obtained in Comparative Example 1 are weighed into a 20 mL glass vial and dispersed in 10 mL of isopropanol (IPA). The solution is exchanged every 3 h at room temperature, and after 24 h, colorless bulk crystals [Cd(tpt)(tpdc-4F)(IPA)2]n are obtained.
[0069] Comparative Example 3
[0070] A method for preparing a derivative of a photo / acid / solvent triple-responsive MOF material includes the following steps: 20 mg of colorless bulk crystals obtained in Comparative Example 1 are weighed into a 20 mL glass vial and dispersed in 10 mL of DMF. The dispersion is performed every 3 hours at room temperature, and after 24 hours, colorless bulk crystals {[Cd(tpt)2(tpdc-4F)(H2O)2]DMF}n are obtained.
[0071] Comparative Example 4
[0072] A method for preparing a derivative of a photo / acid / solvent triple-responsive MOF material includes the following steps: 20 mg of the colorless bulk crystals obtained in Example 2 are weighed into a 20 mL glass vial and dispersed in 10 mL of MeOH. The solution is heated in an oven at 85 °C for 20 h, and then cooled to room temperature to obtain colorless bulk crystals [Zn(tpt)(tpdc-4F)2(MeOH)2]n.
[0073] Experimental Analysis:
[0074] 1. NMR characterization and analysis of ligands TPT and H2Tpdc-4F:
[0075] The NMR spectra of ligands TPT and H2TPDC-4F were measured using a Bruker Avance 400MHz NMR spectrometer, with deuterated reagents CDCl3 and DMSO, respectively. The test results are as follows: Figure 2 In (b) and (d), the proton NMR spectra of the two ligands correspond on the spectrum. Apart from the solvent peak, there are no other impurity peaks, indicating that the synthesized ligand is the target ligand with high purity and accurate structure. The corresponding hydrogen atom chemical shifts are marked on the spectrum. Figure 2 As shown in (a) and (c), the chemical shifts of the two ligands in the proton NMR spectra are as follows: ligand tpt δ 8.98 (dd, J = 4.5, 1.5 Hz, 6H), 8.61 (dd, J = 4.5, 1.6 Hz, 6H); ligand H2tpdc-4F δ
[0076] 13.92 (s, 2H), 7.95 (s, 4H), 7.69 (d, J=9.6Hz, 4H).
[0077] 2. Analysis of single-crystal X-ray diffraction test results of MOF materials prepared in Examples 1 and 2:
[0078] The MOF material prepared in Example 1 crystallized in the monoclinic C2 / c space group. For example... Figure 3 The asymmetric unit consists of a Cd(II) ion, a TPT ligand, and a TPdc-4F ion. 2- It consists of a ligand and two coordinating EtOH molecules. Each Cd(II) ion is associated with two pyridine nitrogen atoms from the tpt ligand and two tpdc-4F atoms. 2- The two carboxyl oxygen atoms in the ligand and the two oxygen atoms in the two EtOH molecules form a six-coordinate octahedral geometry. Each tpdc-4F 2- The carboxylic acid oxygen atom on the ligand is coordinated to two Cd(II) ions in a monodentate coordination mode, and the two pyridine N atoms in each tpt ligand are coordinated to two Cd(II) ions respectively.
[0079] In each tpt ligand, only two N atoms participate in coordination, leaving one pyridine N atom that does not participate in the coordination of the Cd(II) ion. This pyridine N atom is readily protonated in an acidic atmosphere. The Cd(II) ion is simplified to a node with planar 4-connectivity, and tpdc-4F... 2- The ligand and TPT ligand are simplified to 2-connected nodes, as shown in the reference. Figure 4 The MOF material prepared in Example 1 exhibits a 4-cCdS type topology and has a triple interpenetrating structure; such as Figure 5 The MOF material prepared in Example 1 can be regarded as a rhombic framework composed of linear carboxylic acid ligands and metal Cd(II) ions. The tpt ligand is embedded into this rhombic framework by coordinating with Cd(II) ions.
[0080] The MOF material prepared in Example 2 is crystallized in the monoclinic C2 / c space group, and the asymmetric unit consists of a Zn(II) ion, a tpt ligand, and a tpdc-4F ion. 2- It consists of a ligand and two coordinating EtOH molecules. Each Zn(II) ion is associated with two pyridine nitrogen atoms and two tpdc-4F atoms. 2- The two carboxyl oxygen atoms in the ligand and the two oxygen atoms in the two EtOH molecules form a six-coordinate octahedral geometry, each tpdc-4F 2- The ligands coordinate with two Zn(II) ions in a monodentate coordination mode, and the two pyridine N atoms in each tpt ligand are coordinated with two Zn(II) ions respectively.
[0081] The MOF material derivative prepared in Comparative Example 1 is in the monoclinic crystal system, space group P21 / n. The asymmetric unit contains a Cd(II) ion, a tpt ligand, and a tpdc-4F ion. 2- The MeOH molecule consists of ligands and two coordinated atoms. Each Cd(II) ion exhibits a six-coordinated octahedral geometry, coordinated not only to the pyridine nitrogen atoms from the two tpt ligands but also to the two tpdc-4F ligands. 2- The two carboxyl oxygen atoms in the ligand are linked in a monodentate coordination mode, and the two oxygen atoms in the two MeOH molecules also participate in the coordination of the Cd(II) ion. Furthermore, each tpdc-4F 2- The coordination modes of the ligands and tpt ligands were the same as in Example 1. Compared with Example 1, after MeOH exchange, the terminally coordinated EtOH molecules were replaced by MeOH molecules, and free MeOH molecules were present in the channels of Comparative Example 1.
[0082] 3. Thermogravimetric analysis:
[0083] Thermal stability data were obtained by testing the carbon heat loss and thermal stability of the samples using an HCT-1 thermogravimetric analyzer. Before testing, the samples were dried in a vacuum drying oven at 70℃ for 12 hours. 5-10 mg of each sample was weighed and placed in a crucible, and the test was conducted under a N2 atmosphere at a temperature range of 35℃-800℃ and a heating rate of 10℃ / min. The test results are as follows: Figure 6 All four complexes showed slight weight loss below 100℃, mainly due to the loss of some solvent molecules during heating. The complexes exhibited a plateau in thermogravimetric analysis between 100-350℃, indicating that the complexes were stable within this temperature range. After 350℃, the compounds slowly lost weight, indicating that the complexes began to decompose.
[0084] 4. Acid vapor response performance testing and analysis
[0085] (1) Acid vapor response performance test of MOF material in Example 1: By exposing the crystal sample to 12% HCl vapor, such as Figure 7 In (a), the crystal's color rapidly changed from colorless to yellow, and the fluorescence emission color changed from cyan to yellow-green. The fluorescence intensity decreased with increasing exposure time. Then, the protonated yellow crystal sample was fumigated in NH3 for 120 seconds, undergoing a deprotonation reaction. Under fluorescent light, the sample color returned to colorless. Figure 7 In (b) and (c), the absorption intensity significantly increases in the 400-500 nm range, and the fluorescence emission intensity also increases accordingly. The changes in fluorescence intensity of the MOF material in Example 1 after exposure to different acidic vapors for the same time are shown below. Figure 7 In the middle (d), HBr vapor has a stronger electron-donating ability than HCl vapor, and the quenching efficiency of HBr vapor is greater than that of HCl vapor.
[0086] like Figure 8 (a) in the text refers to rtpdc-4F before protonation. 2- The units mainly form HOMOs, while LUMOs primarily originate from the triazine ring and coordinated pyridine ring of the tpt molecule. For example... Figure 8 In (b), after protonation, the orbital distribution of HOMO remains essentially unchanged, while LUMO orbitals are distributed on the triazine ring and the uncoordinated pyridine ring of the tpt molecule. Before protonation, the orbital energy difference between HOMO and LUMO is 3.1172 eV. After protonation, the HOMO orbitals remain largely unchanged, primarily composed of tpdc orbitals. 2-The LUMO orbital primarily originates from a triazine ring and one of the pyridine units, with its energy level difference reduced to 0.4416 eV. Protonation significantly reduces the HOMO-LUMO energy level difference, further demonstrating a redshift in wavelength after protonation, consistent with emission spectroscopy results. Furthermore, the HOMO and LUMO orbitals are distributed in different ligands, and the MOF material of Example 1 exhibits ligand-ligand charge transfer (LLCT) upon excitation, where tpdc-4F... 2- It is an electron donor, and tpt is an electron acceptor.
[0087] (2) Acid vapor response performance test of MOF material in Example 2: The MOF material powder sample of Example 2 was placed in an open cuvette, and then the cuvette was floated in a closed space containing HCl for fumigation time of less than 30s. The color of the sample rapidly changed from colorless to yellow, and under 365nm ultraviolet light irradiation, it changed from blue to yellow-green. Figure 9 In (a), as the fumigation time increases, the absorption peak of the powder sample in Example 2 at a wavelength of 380 nm gradually broadens and shifts to a longer wavelength, which is consistent with Example 1. The change in the UV-Vis absorption spectrum is caused by the protonation of the uncoordinated pyridine nitrogen atoms in the powder sample of Example 2.
[0088] like Figure 9 In (b), as the fumigation time increases, the fluorescence intensity gradually decreases, and the fluorescence emission wavelength also undergoes a red shift, indicating that the fluorescence emission spectrum is affected by the surrounding acidic atmosphere or caused by photoinduced electron transfer between different ligands. Figure 9 In Example (c), the lifetime shortened after protonation in Example 2, decreasing from 35.6 ns to 25.6 ns, consistent with the results of Example 1. The hydrochloric acid vapor response spectra of the powder samples from Examples 1 and 2 were almost identical, indicating that the acid response performance is independent of the central metal ion and mainly related to the configuration of the MOF and the interactions between the organic ligands. Figure 9 In Example 2, before protonation (d), the orbital energy level difference between HOMO and LUMO was 0.1216 eV. After protonation, as shown in example (d), the orbital energy level difference between HOMO and LUMO was 0.1216 eV. Figure 9 In (e), HOMO mainly originates from a tpdc-4F 2- The unit, LUMO, mainly originates from a triazine ring and a pyridine ring in the tpt molecule, with its energy level difference reduced to 0.0181 eV. Therefore, the changes in the DFT calculation results of Examples 1 and 2 are mainly due to the change in framework configuration.
[0089] 5. Photochromic performance testing and analysis
[0090] (1) Photochromic performance test of MOF material in Example 1: The powder sample of Example 1 was irradiated with a 300W xenon lamp for 120s. The color of the crystalline sample gradually changed from colorless to purple in a short time. Figure 10 This is a schematic diagram of the response of the MOF material in Example 1 under different wavelengths of light, showing that the optimal excitation wavelength is in the range of 360-370 nm. Figure 11 In (a) of Example 1, a new absorption band appeared in the 450-650 nm range under xenon lamp irradiation. This absorption band gradually increased with irradiation time, and then gradually weakened after 240 s, indicating the formation of pyridine radicals. Therefore, 365 nm light was selected as the excitation wavelength to further test the fluorescence emission spectrum of the Example 1 sample, as shown in (a). Figure 11 In (b) of Example 1, the sample exhibited an emission peak at 475 nm before xenon lamp irradiation. The fluorescence intensity decreased with increasing irradiation time, and tended to saturate after 2 minutes. Figure 11 (c) shows a schematic diagram of monitoring the reversibility of photochromic behavior using fluorescence spectroscopy. First, the solid-state fluorescence spectrum of the original material was tested, followed by the fluorescence spectrum of the sample after xenon lamp irradiation. During this process, the fluorescence intensity decreased, and finally, after heat treatment, the fluorescence intensity returned to its initial value in the fluorescence emission spectrum. After five cycles of this reversible operation, the purple crystal sample could quickly recover its initial colorless color upon heating at 120℃ for 1 minute or placing it in the dark. The decolorization time was shorter than or equal to that of some advanced photochromic materials, indicating that photoelectron transfer occurred between the two ligands. Figure 11 In (d), a significant signal is observed after xenon lamp irradiation at a wavelength of 365 nm, whereas no signal was observed before this point. This indicates the generation of free radicals after irradiation, which can be attributed to the electron-rich formic acid unit (TPDC-4F). 2- Electrons are transferred to electron-deficient units (tpt).
[0091] Figure 12 (a) in the figure is the X-ray diffraction pattern of the MOF material in Example 1 before and after xenon lamp irradiation. Figure 12 (b) shows the Fourier transform infrared spectra of the MOF material in Example 1 before and after xenon lamp irradiation. The spectra before and after irradiation are consistent with those simulated using single crystal data. Furthermore, the spectrum of the powder sample hardly changes after heat treatment, indicating that the framework of the crystal sample in Example 1 does not undergo significant changes during the photochromic cycle. The fact that the FT-IR spectrum hardly changes before and after xenon lamp irradiation further demonstrates that the crystal sample in Example 1 has good stability during photochromism and heat recovery.
[0092] (2) Photochromic performance test of MOF material in Example 2: The powder sample of Example 2 was irradiated with a 300W xenon lamp for 120s. The color of the crystalline sample gradually changed from colorless to purple in a short time, such as... Figure 13 In (a) of Example 2, after 120 s of xenon lamp irradiation, the crystal sample changed from colorless to purple. When the powder sample was irradiated with 360 nm ultraviolet light, the color changed after 35 s, slightly faster than in Example 1. This indicates that the crystal samples of Examples 1 and 2 are most sensitive to light with λ = 360 nm. After the color change, the sample returned to its initial colorless state after heating at 100°C for 3 min in the presence of DMF solvent or after standing in the dark. In the ultraviolet absorption spectrum of Example 2, the peak around 500 nm gradually increased with xenon lamp irradiation, indicating that free radicals were also generated in Example 2. Therefore, the photochromic mechanism of the crystal samples in Examples 1 and 2 can both be explained as electron transfer occurring between the electron-rich carboxylic acid and the electron-deficient triazine ring. Figure 13 In (b) of the example, under light excitation at a wavelength of 365 nm, the fluorescence emission intensity of Example 2 gradually decreased with the increase of xenon lamp irradiation time. After irradiation time of 180 s, the decrease in fluorescence intensity decreased and eventually remained almost unchanged.
[0093] like Figure 14 To illustrate the use of fluorescence spectroscopy to monitor the reversibility of photochromic behavior, the solid-state fluorescence spectrum of the original material was first tested, followed by the fluorescence spectrum of the sample after xenon lamp irradiation. During this process, the fluorescence intensity decreased, and after heat treatment, the fluorescence intensity returned to its initial value in the fluorescence emission spectrum. After five cycles of this reversible operation, the fluorescence intensity remained almost unchanged, indicating that the crystal sample of Example 2 exhibits excellent reversibility during photochromism.
[0094] like Figure 15 In Example (a), the MOF material before and after irradiation is consistent with the simulation, indicating that the framework structure did not change during the color change process. This test result is consistent with the electron transfer mechanism characteristics of photochromism, and also rules out the possibility that the photochromism of compound 4 is caused by photolysis or rearrangement reaction of the sample after xenon lamp irradiation; Figure 15 In (b), the blue line shows no free radical EPR signal. Subsequently, the crystal sample of Example 2 was irradiated under a xenon lamp for 10 minutes, as shown by the red line. Free radicals were generated after xenon lamp irradiation, and electron transfer occurred during the photochromic process. After xenon lamp irradiation, electrons were transferred from the electron-rich building block tpdc-4F to the electron-deficient tpt molecule.
[0095] 6. Solvent-induced fluorescence color change performance testing and analysis
[0096] (1) Solvent-induced fluorescence color change performance test in Example 1: Solid-state three-dimensional fluorescence spectroscopy analysis was performed on the sample of Example 1. When the excitation wavelength increased from 330 nm to 370 nm, the emission peak position of the fluorescence spectrum remained unchanged, such as... Figure 16 In (a), the emission spectra of Example 1 dispersed in different solvents were tested using an excitation wavelength of 365 nm; as shown in (a). Figure 16 In (b) of the figure, it can be clearly observed that the emission wavelength changes in the methanol solution, shifting from 475 nm (blue) to 490 nm (green), as shown in the figure. Figure 16 In (c), the normalized emission spectra of Example 1 dispersed in pure MeOH, DMF, and mixed solvents of different proportions show that the emission wavelength gradually red-shifts from 470 nm to 492 nm with increasing methanol content. Under 365 nm ultraviolet light irradiation, the fluorescence color of Example 1 also changes from cyan to green. Notably, after immersion in DMF, the weak green emission can recover to the initial blue emission, indicating that the solvent-induced fluorescence color change behavior of Example 1 is a reversible process. Figure 16 The (d)-(f) results further demonstrate the reversibility of the solvent-induced fluorescence color change behavior in Example 1. The fluorescence peaks of the original sample and the methanol-exchanged sample are at 475 nm and 495 nm, respectively. The normalized emission spectra of Example 1 dispersed in different EtOH / MeOH mixed solvents (ethanol, 1% MeOH, 25% MeOH, 50% MeOH, MeOH) are shown below. Figure 17 In (a), as the methanol content increases, the fluorescence spectrum shows a red shift, exhibiting obvious fluorescence color change behavior.
[0097] Under otherwise unchanged conditions, single crystals were cultured using methanol instead of ethanol, and crystals with the same configuration were prepared, yielding Comparative Example 1. Comparative Example 1 could also be obtained by soaking Example 1 in methanol. Compared to Example 1, in Comparative Example 1, the coordinated ethanol molecules were replaced by methanol, and the space group changed to P21 / n, with a change in the smallest asymmetric unit. The fluorescence spectra of the directly synthesized Comparative Example 1 and the methanol-exchanged Comparative Example 1 were tested, as shown in 21(b). At an excitation wavelength of 365 nm, the emission wavelengths of both samples were around 485 nm.
[0098] Furthermore, in Comparative Example 1, the presence of numerous free methanol molecules in the channels significantly suppressed intramolecular vibrations within the framework through intermolecular hydrogen bonding, resulting in a redshift in the spectrum. The Hirshfeld surface was used for further analysis of supramolecular interactions in Example 1 and Comparative Example 1. Figure 18 In the figures (a) and (b), respectively, Example 1 and Comparative Example 1 are shown in d. normThe surfaces are mapped onto the shape-index. To clearly observe the molecular portions, the surfaces are shown in a transparent color. Larger red dots in the figure represent strong intermolecular H-bond interactions, while smaller red dots represent relatively weaker H-bond interactions. Two-dimensional fingerprint analysis shows that the supramolecular interactions in Example 1 and Comparative Example 1 are mainly HH interactions, accounting for 23.4% and 29.2% of all interactions, respectively. This is followed by CH interactions, accounting for 20.5% and 21.5%, respectively. Notably, OH interactions account for 13.3% and 11.2% of the Hirshfeld surfaces in Example 1 and Comparative Example 1, respectively, and HF interactions account for 12.3% and 13.1% in the two MOFs, respectively. The remaining interactions between different atoms, such as HN, CC, CF, CO, and CN, are relatively weak forces and contribute little to the surfaces of Example 1 and Comparative Example 1.
[0099] In Example 1, as Figure 19 (a) and (b) in the text, tpdc-4F 2- The main contributor to the HOMO orbital is the tpdc-4F2- unit, while the LUMO orbital primarily originates from the triazine ring of the tpt molecule and a pyridine ring involved in coordination. In Example 1, the energy level difference between the HOMO and LUMO orbitals is 3.1172 eV. In Comparative Example 1, the HOMO orbital formation mainly originates from one of the tpdc-4F2- units, while the LUMO orbital mainly originates from a triazine ring with two pyridine moieties involved in coordination and one uncoordinated pyridine unit, with the energy level difference reduced to 0.1102 eV. After methanol exchange in Example 1, the HOMO-LUMO energy level difference significantly decreased, consistent with the redshift results in the emission spectrum. Similarly, in Example 1 and Comparative Example 1, the HOMO and LUMO are distributed in different ligands, revealing a ligand-ligand charge transfer (LLCT) mechanism occurring upon excitation in Example 1, where the tpdc-4F2- unit... 2- It is an electron donor, while tpt is an electron acceptor.
[0100] Furthermore, in Comparative Example 1, the fluorescence returned to its original cyan emission after being exchanged with IPA and DMF, respectively. 20 mg of Comparative Example 1 was exchanged with IPA and DMF at room temperature, with the solvent changed every 3 hours. After 24 hours, [Cd(tpt)(tpdc-4F)(IPA)2]n (Comparative Example 2) and {[Cd(tpt)2(tpdc-4F)(H2O)2]DMF}n (Comparative Example 3) were obtained. Single-crystal X-ray diffraction data showed that both crystals belonged to the monoclinic C2 / c space group, the same as in Example 1. In Comparative Example 2, IPA replaced the coordinated ethanol molecules; in Comparative Example 3, water replaced the coordinated ethanol molecules, and free DMF solvent molecules were added to the channels; the minimum asymmetric unit of the two frameworks also changed. Fluorescence spectroscopy confirmed that the fluorescence emission could be restored to the initial wavelength after two solvent exchanges. DFT calculations showed that the energy level differences between Comparative Example 2 and Comparative Example 3 were 3.000 eV and 3.229 eV, respectively. These energy level differences were larger than those of Comparative Example 1 and similar to those of Example 1 (3.079 eV), further indicating that the fluorescence of Comparative Example 1 underwent a blue shift after IPA and DMF exchange, similar to... Figure 19 The spectral test results in (c) are consistent.
[0101] (1) Solvent-induced fluorescence color change performance test in Example 2: Example 2 was dispersed in different organic solvents (DEF, DMF, EtOH, CH2Cl2, MeCN, IPA, and MeOH), and the fluorescence emission spectrum was measured at an excitation wavelength of 365 nm, as shown below. Figure 20 Based on the above results, the fluorescence spectra of mixed solvents of Example 2 with different ratios of methanol and ethanol (0%, 1%, 10%, 25%, 50%, and 100% MeOH) were tested, as shown below. Figure 21 In Example (a), the emission wavelength of the fluorescence dispersed in ethanol is around 460 nm. As the methanol content increases, the wavelength red-shifts. When the methanol content increases to 100%, the fluorescence emission wavelength red-shifts to around 490 nm. On the CIE coordinate axis, the color of the fluorescence emission can be observed to gradually change from blue to green.
[0102] like Figure 21In Example (a), the emission wavelength of Example 2 dispersed in methanol is around 490 nm, with a greenish fluorescence color. In other solvents, the emission wavelength is around 460 nm, with a cyan fluorescence color. Color changes in different solvents were observed on the CIE coordinate system. This demonstrates that Example 2 also responds well to methanol. Comparative Example 4 was obtained by exchanging Example 2 with methanol. Its single-crystal data shows that the ethanol molecules coordinated in the structure of Example 2 were transformed into methanol molecules in Comparative Example 4 after solvent exchange. From Example 2 to Comparative Example 4, the smallest asymmetric unit changed, but the overall framework remained almost unchanged. Based on the above results, the fluorescence spectra of Example 2 in mixed solvents with different methanol and ethanol ratios (0%, 1% MeOH, 10% MeOH, 25% MeOH, 50% MeOH, 100% MeOH) were further tested. Figure 21 In Example (b), the emission wavelength of the fluorescence dispersed in ethanol is around 460 nm. As the methanol content increases, the wavelength red-shifts. When the methanol content increases to 100%, the fluorescence emission wavelength red-shifts to around 490 nm. On the CIE coordinate axis, the color of the fluorescence emission can be observed to gradually change from blue to green.
[0103] like Figure 22 In Example 2 (a), the HOMO is mainly distributed on the triazine rings of the two pyridine triazine molecules and the π* orbitals of the two coordinating pyridines. The LUMO is distributed on the tpdc orbitals of the two coordinating pyridines. 2- Regarding the ligands, the energy level difference between HOMO and LUMO is 3.319 eV. For example... Figure 22 In (b) of Comparative Example 4, the HOMO is mainly distributed on the triazine ring of one pyridine triazine molecule and the π* orbitals of the three pyridines. The LUMO mainly originates from one of the coordinating tpdc-4F molecules. 2- The energy difference between the ligands HOMO and LUMO is 2.939 eV. From Example 2 to Comparative Example 4, the energy level difference is significantly reduced, consistent with the results of redshift in the fluorescence spectra.
[0104] Figure 23 In the figures (a) and (b), respectively, Example 2 and Comparative Example 4 are shown in d. normThe surface is mapped onto the shape-index. Prominent peaks on the two-dimensional fingerprint represent important intermolecular interactions. Taking the OH / HO intermolecular interaction in Example 2 as an example, the OH interaction is represented by a peak in the lower left (donor) region of the fingerprint, while the HO interaction is represented by a peak in the lower right (acceptor) region. Two-dimensional fingerprint calculations show that the main supramolecular interaction in Example 2 and Comparative Example 4 is the HH interaction, accounting for 29.2% and 28.1% of all interactions, respectively. The second most significant interaction is the CH interaction, contributing 18.3% and 21.7% to Example 2 and Comparative Example 4, respectively. Furthermore, the OH interaction accounts for 13.5% and 10.8% of the Hirshfeld surface in Example 2 and Comparative Example 4, respectively, and the HF interaction accounts for 10.7% and 13.1% in the two MOFs, respectively. The remaining interactions, such as HN, CC, CF, CO, and CN, are relatively weak forces and contribute little to the surfaces of Example 2 and Comparative Example 4.
[0105] 7. Application of Example 1 as a smart anti-counterfeiting material
[0106] Utilizing the multiple stimulus-response characteristics of Example 1, its potential applications in anti-counterfeiting were investigated, such as... Figure 24 The solid powder from Example 1 was sprinkled onto a surface labeled... On the quartz glass substrate. When When exposed to a xenon lamp, the color rapidly changes from colorless to purple. However, in high-temperature or dark environments, the purple powder reverts to colorless. When methanol is dropped onto the surface of the letter "K," it emits green fluorescence under 365nm ultraviolet light, while treatment with ethanol results in blue fluorescence. The character "U" turns yellow in an HCl vapor atmosphere, its fluorescence emission changes from blue to green, and it reverts to colorless upon exposure to NH3 vapor. Example 1 demonstrates the ability to rapidly change color or fluorescence properties under different external stimuli, thus possessing potential as a smart anti-counterfeiting material.
[0107] In summary, solvent-induced fluorescence, photochromism, and acid-responsive color change were simultaneously observed in the MOF materials prepared in this application. The solvent-induced fluorescence in Examples 1 and 2 is a rapid and reversible process, mainly due to the interaction of free methanol molecules within the pores. DFT calculations further demonstrate that the red shift in the fluorescence spectrum after solvent exchange is caused by changes in energy level differences. Notably, Examples 1 and 2 exhibit blue fluorescence in ethanol and green fluorescence in methanol, which can be used for the detection of trace amounts of methanol in ethanol. The colors of Examples 1 and 2 rapidly change from colorless to purple under 300W xenon lamp irradiation; this change is visible to the naked eye and reversible. EPR testing confirms that the photochromism is mainly due to electron transfer from the carboxylic acid ligand to the pyridine triazine ligand under illumination, generating free radicals. Furthermore, because the tpt ligand in the framework of Examples 1 and 2 has uncoordinated N atoms, it undergoes protonation upon contact with HCl vapor, resulting in a significant color change, which can be restored to its initial color by treatment with NH3 vapor.
[0108] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A photo / acid / solvent triple-responsive MOF material, characterized in that, The chemical formula of the MOF material is: [M(tpt)(tpdc-4F)(NOH)] n ; Wherein, M is any one of the group IIB elements Cd and Zn; tpt is 2,4,6-tris(4-pyridyl)-1,3,5-triazine; tpdc-4F is 3,3”,5,5”-tetrafluoro-[1,1':4',1”-triphenyl]-4,4”-dicarboxylic acid; NOH is a C1-C4 alcohol molecule.
2. The photo / acid / solvent triple-responsive MOF material according to claim 1, characterized in that, If M is Cd, a Group IIB element, then the chemical formula of the MOF material is [Cd(tpt)(tpdc-4F)(NOH)]. n .
3. The photo / acid / solvent triple-responsive MOF material according to claim 1, characterized in that, If M is Zn, a Group IIB element, then the chemical formula of the MOF material is [Zn(tpt)(tpdc-4F)(NOH)]. n .
4. A method for preparing a photo / acid / solvent triple-responsive MOF material, characterized in that, Includes the following steps: S1. After heating and reacting 18-crown-6, KOH, and 4-cyanopyridine in decahydronaphthalene, the tpt ligand was obtained by acid / base treatment. S2. Condensate 1,4-dibromobenzene and 3,5-difluoro-4-methoxycarboxyphenylboronic acid pinacol ester under palladium catalyst, and then hydrolyze to obtain H2tpdc-4F ligand. S3. MOF crystals are obtained by heating tpt, H2tpdc-4F and M(NO3)2·4H2O in a DMF / ethanol mixed solvent.
5. The method for preparing a photo / acid / solvent triple-responsive MOF material according to claim 4, characterized in that, In S1, the mass ratio of 18-crown-6 to 4-cyanopyridine is 1:
10.
6. The method for preparing a photo / acid / solvent triple-responsive MOF material according to claim 4, characterized in that, In S2, the molar ratio of 1,4-dibromobenzene and 3,5-difluoro-4-methoxybenzeneboronic acid pinacol ester is 1:
3.
7. The method for preparing a photo / acid / solvent triple-responsive MOF material according to claim 4, characterized in that, In S3, the molar ratio of pt, H2tpdc-4F and M(NO3)2·4H2O is 1:1:(1.5-2.5).
8. The method for preparing a photo / acid / solvent triple-responsive MOF material according to claim 4, characterized in that, In S3, M(NO3)2·4H2O is either Cd(NO3)2·4H2O or Zn(NO3)2·4H2O.
9. The application of a photo / acid / solvent triple-responsive MOF material as described in any one of claims 1-3, characterized in that, In applications of manufacturing optical products, such as fluorescent luminescent products.
